2016
DOI: 10.26754/ojs_geoph/geoph.2003441351
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de los embalses en el control de las avenidas en el Pirineo Central Español

Abstract: Resumen: Se estudia el efecto de los embalses en la reducción de la intensidad de avenidas que afectan a los ríos pirenaicos. Se trata de un fenómeno complejo en el que interviene la capacidad de retención de cada embalse, las funciones que desarrollan, el régimen de llenado y vaciado y su ubicación cuando aparecen formando un sistema inúltiple. La combinación de estos factores explica los distintos porcentajes de reducción de los caudales inás elevados observados en la zona de estudio. A pesar de la existenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Table 2.2). Data were normalised to a reference altitude of 1400 m based on an atmospheric annual temperature lapse rate and precipitation gradient set to 0.63 °C•100 m -1 and 46 mm•100 m -1 , respectively (López- Moreno, 2006), thus generating spatially-averaged values of CPM and MMT (see Suppl. Table 2.3).…”
Section: Glaciological and Paleoclimate Modelingmentioning
confidence: 99%
“…Table 2.2). Data were normalised to a reference altitude of 1400 m based on an atmospheric annual temperature lapse rate and precipitation gradient set to 0.63 °C•100 m -1 and 46 mm•100 m -1 , respectively (López- Moreno, 2006), thus generating spatially-averaged values of CPM and MMT (see Suppl. Table 2.3).…”
Section: Glaciological and Paleoclimate Modelingmentioning
confidence: 99%
“…The substantially lower storage volumes of these reservoirs may not be the only responsible for these results. Other dam uses (e.g., Bubal, Lanuza, and Escales are also used for flood control and hydropower production; López Moreno et al, 2016) might also contribute to the observed differences. Accordingly, we found that HIs associated with hydropower, such as nPos and nNeg, were significantly altered in the Pyrenees, in agreement with previous studies (Almeida et al, 2020;Chalise et al, 2021;Pompeu et al, 2022b).…”
Section: Abiotic Changes Associated With Damsmentioning
confidence: 99%
“…The temperature gradient proposed for the entire Pyrenean range varies according to the author: 0.6 (García-Ruiz et al 1986), 0.68 (Del Barrio et al 1990) and 0.63°C/100 m (López-Moreno 2006). Based on these gradients, the annual 0°C isotherm is located around 2900 m (Chueca-Cía et al 2003).…”
Section: Study Areamentioning
confidence: 99%